Phosphorylation of multiple proteins involved in ciliogenesis by Tau Tubulin kinase 2 - Bernatik, Ondrej; Pejskova, Petra; Vyslouzil, David; Hanakova, Katerina; Zdrahal, Zbynek; Cajanek, Lukas (Molecular biology of the cell, 2020)
Primary cilia are organelles necessary for proper implementation of developmental and homeostasis processes. To initiate their assembly, coordinated actions of multiple proteins are needed. Tau tubulin kinase 2 (TTBK2) is a key player in the cilium assembly pathway, controlling the final step of cilia initiation. The function of TTBK2 in ciliogenesis is critically dependent on its kinase activity; however, the precise mechanism of TTBK2 action has so far not been fully understood due to the very limited information about its relevant substrates. In this study, we demonstrate that CEP83, CEP89, CCDC92, Rabin8, and DVL3 are substrates of TTBK2 kinase activity. Further, we characterize a set of phosphosites of those substrates and CEP164 induced by TTBK2 in vitro and in vivo. Intriguingly, we further show that identified TTBK2 phosphosites and consensus sequence delineated from those are distinct from motifs previously assigned to TTBK2. Finally, we show that TTBK2 is also required for efficient phosphorylation of many S/T sites in CEP164 and provide evidence that TTBK2-induced phosphorylations of CEP164 modulate its function, which in turn seems relevant for the process of cilia formation. In summary, our work provides important insight into the substrates-TTBK2 kinase relationship and suggests that phosphorylation of substrates on multiple sites by TTBK2 is probably involved in the control of ciliogenesis in human cells.
Keywords: kaseinkinasa I; cilie; Phosphorylation; Humans; Substrate Specificity; fosforylace; organogeneze; Phosphothreonine; protein-serin-threoninkinasy; lidé; Casein Kinase I; HEK293 Cells; Cilia; fosfothreonin; Protein Serine-Threonine Kinases; substrátová specifita; HEK293 buňky; fosfoserin; Organogenesis; aminokyselinové motivy; multiproteinové komplexy; Amino Acid Motifs; Multiprotein Complexes; Phosphoserine